COVID-19 sequelae in adults aged less than 50 years: A systematic review. Issue 40 (March 2021) - Willi, Sandra; Lüthold, Renata; Hunt, Adam; Hänggi, Nadescha Viviane; Sejdiu, Donikë; Scaff, Camila; Bender, Nicole; Staub, Kaspar; Schlagenhauf, Patricia
Abstract: Background: There is emerging evidence of long-term sequelae in a considerable proportion of COVID-19 patients after recovery and the spectrum and severity of such sequelae should be systematically reviewed. This review aims to evaluate the available evidence of all intermediate and long-term COVID-19 sequelae affecting formerly healthy adults. Methods: A systematic literature search of Embase, WHO, Scopus, Pubmed, Litcovid, bioRxiv and medRxiv was conducted with a cutoff date of the 17th September 2020 according to PRISMA guidelines and registered in PROSPERO (CRD42020208725). Search terms included "COVID-19", "coronavirus disease 2019", "SARS-CoV-2", "sequelae" and "consequence*". Publications on adult participants, with a confirmed SARS-CoV-2 infection were included. Elderly (>50 years old) and children (<18 years old) were excluded. Bias assessment was performed using a modified Newcastle-Ottawa Scale. Results: A total of 31 papers were included. Study types included prospective and retrospective cohort studies, cross-sectional studies and case reports. Sequelae persistence since infection spanned 14 days to three months. Sequelae included persistent fatigue (39–73% of assessed persons), breathlessness (39–74%), decrease in quality of life (44–69%), impaired pulmonary function, abnormal CT findings including pulmonary fibrosis (39–83%), evidence of peri-/perimyo-/myocarditis (3–26%), changes in microstructural and functional brain integrity with persistent neurological symptoms (55%), increased incidence of psychiatric diagnoses (5.8% versus 2.5–3.4% in controls), incomplete recovery of olfactory and gustatory dysfunction (33–36% of evaluated persons). Conclusions: A variety of organ systems are affected by COVID-19 in the intermediate and longer-term after recovery. Main sequelae include post-infectious fatigue, persistent reduced lung function and carditis. Careful follow-up post COVID 19 is indicated to assess and mitigate possible organ damage and preserve life quality.